Ventilation characteristics of buildings incorporating different configurations of curved roofs and wind catchers: (with reference to human comfort) - Asfour, Omar S.M. (2006)
This study investigates the effect of utilising different configurations of curved roofs and wind catchers on natural ventilation performance of buildings. It compares airflow rates and internal airflow velocity and distribution, before and after, employing domed and vaulted roofs for wind-induced natural ventilation and, thus, thermal comfort improvement. This also includes the role of integrating different wind-catcher systems into the investigated curved roofs. A review of the related background studies and literature has revealed the architectural importance of these elements, and their potential for natural ventilation and passive cooling in hot climates, with particular reference to the Middle East. A review of the different natural ventilation prediction methods has also exposed the challenge associated with air infiltration modelling and understanding.